INTRODUCING PheT AS A PHYSICS LECTURE SIMULATION SOFTWARE: IMPLICATION FOR EFFECTIVE STEM EDUCATION (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
This study explores the impact of using PhET simulations in physics lectures on student engagement and understanding in STEM education. A quasi-experimental design was employed, involving 200 secondary school students from Rivers State, Nigeria. The students were divided into a control group and an experimental group. The experimental group used PhET simulations during their physics lectures, while the control group followed the traditional lecture method. Data on student engagement, understanding of physics concepts, and academic performance were collected through pre- and post-tests, classroom observations, and student feedback surveys. Statistical analysis was conducted using SPSS version 25.0. The results indicated a significant improvement in the academic performance and engagement levels of students in the experimental group compared to the control group. The mean post-test scores of the experimental group were 30% higher than their pre-test scores, while the control group showed a 15% improvement. Classroom observations revealed that students using PhET simulations were more actively engaged and demonstrated a better understanding of complex physics concepts. Student feedback highlighted the interactive and intuitive nature of PhET simulations as key factors contributing to their enhanced learning experience. The study demonstrates that integrating PhET simulations into physics lectures can significantly improve student engagement and understanding in STEM education. The findings suggest that PhET simulations are an effective tool for making physics concepts more accessible and engaging for students. Educators and policymakers should consider incorporating PhET simulations into the STEM curriculum to enhance the quality of education and foster a deeper interest in science among students.